2007
DOI: 10.1111/j.1468-5965.2007.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action Plan on Combating Terrorism: A Flawed Instrument of EU Security Governance

Abstract: After clarifying the ideal-typical characteristics of action plans, this contribution shows how the Action Plan on Combating Terrorism emerged out of a hectic process of policy-entrepreneurship by the European Commission and other integration-minded actors. This overloaded the EU's policy-making capacity and fostered policy conflict, while the strategic dimension was neglected. Copyright (c) 2008 The Author(s); Journal compilation (c) 2008 Blackwell Publishing Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 22 publications
(26 reference statements)
0
36
0
Order By: Relevance
“…These authors have shown that the EU is both more prolific and more powerful in internal security than the commonly held notion of an EU 'capabilities gap' would suggest (Argomaniz 2009;Bossong 2008;Kaunert, Leonard, and Pawlak 2012). This literature describes the novel institutional forms of European security cooperation in terms of networked security and Agency-based cooperation (e.g.…”
Section: European Counterterrorism and Transatlantic Cooperationmentioning
confidence: 99%
“…These authors have shown that the EU is both more prolific and more powerful in internal security than the commonly held notion of an EU 'capabilities gap' would suggest (Argomaniz 2009;Bossong 2008;Kaunert, Leonard, and Pawlak 2012). This literature describes the novel institutional forms of European security cooperation in terms of networked security and Agency-based cooperation (e.g.…”
Section: European Counterterrorism and Transatlantic Cooperationmentioning
confidence: 99%
“…Monar et al (2003),Baldaccini et al (2007),Balzacq and Carrera (2006),Huysmans (2006),Guild and Geyer (2008), van Munste (2009) andBigo et al (2010).2 Zimmermann (2006),Spence (2007),Eckes (2009), Brown (2010,Bures (2006;), Argomaniz (2011), Kaunert (20052010a;2010b;2010c),Kaunert and Della Giovanna (2010),Kaunert and Léonard (2011),Léonard and Kaunert (2012),Kaunert et al (2012a),Bossong (2008; andMacKenzie et al (2013).3 Baldaccini(2007),Geddes (2008),Léonard (2009) andBoswell and Geddes (2011).4 Fletcher and Lö ö f (2008) andEckes and Konstadinides (2011).5 Anderson and Apap (2002),Occhipinti (2003) andGuild and Geyer (2008).6 Kaunert et al (2012b) andKaunert and Zwolski (2013).7 Balzacq(2009), Wolff et al (2009), Wolff (2009; 2012) and Trauner (2011).Introduction 499 Downloaded by [UQ Library] at 03:54 15 March 2015…”
mentioning
confidence: 94%
“…So far, many studies use security governance in a more metaphorical sense without specifying its core elements as an analytical framework and its relation to other relevant theories and concepts (see e.g. Bossong 2008). The special issue therefore asks: What are essential categories of security governance in specific areas?…”
Section: Conceptual Empirical and Normative Challengesmentioning
confidence: 99%